A Study of Socio Cultural Practices in the Personal Development/Empowerment of Adolescent Girls: Exploring Psychosocial and Cultural Barriers Faced by Adolescent Girls in Rural India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The examination endeavors to discover the current social and cultural practices in regards to period, mindfulness levels, and the conduct changes that occur in adolescent girls amid monthly cycle, their discernment about menarche, how they would treat it, and the different taboos, standards, and cultural practices related with menarche. Indeed, even today in the 21st century India, the psychosocial and cultural situations have multitudinous preferential conventions and excess traditions endowment, child marriage, absence of education, physical and mental viciousness, and so on. The Indian girls in light of their auxiliary status in the general public may have low confidence and poor mental prosperity. In this manner it winds up imperative to ponder the psychosocial and cultural boundaries looked by Indian girls keeping in mind the end goal to offer an opportune adjustment that can enable them to assume a considerable part in getting down to business the future village society. The wide goal of the present investigation was to recognize the psychosocial and cultural obstructions in a village society which thwarting to get girls' maximum capacity. Two hundred and ten members, between the age group of 13-19 years, from District Rohtak in Haryana (India), reacted in a particular survey. Meetings and center group talks were additionally held. Around 10 talks were taken with rural ladies. Results acquired demonstrate certain components as inhibitors (e.g. unsafe customary practices, clashing circumstances, sexual orientation segregation and so forth.). The ramifications of the discoveries in giving ways to arrangement creators, social researchers, and health professionals towards rural regions in regards to adolescent girls has been talked about.